Teachers’ conceptions about the sexuality of students with disabilities: effects of teacher training - Maia, Ana Cláudia Bortolozzi [UNESP] (2020)
The present study investigated teachers’ conceptions about sexuality and disabilities and the effects of sexuality education training. Ten teachers between the ages of 41 and 52 were interviewed. Their conceptions about the sexuality of people with disabilities were as follows: exaggerated and uncontrollable sexuality; inappropriate behavior (intellectual disabilities); complicated and exaggerated sexuality and the need for support (autistic); normal sexuality, communication problems and use of other senses (sensory impairment); complex yet potentially positive sexuality (physical disability); complex sexuality that depends on adaptations and social support (multiple disabilities). After participating in theoretical-practical training, the teachers came to view people with disabilities as sexual beings, clarified their beliefs, and planned an intervention project for their students with disabilities. We conclude that in-service teacher training in sexuality and disability can contribute to strengthening theory with pedagogical practice, especially in relation to sexuality education, which is still scarce in inclusive education.